2005
DOI: 10.1007/s10552-005-0318-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Anthropometric, and Lifestyle Factors Associated with IGF-1 and IGFBP-3 Levels in Hispanic and Non-Hispanic White Women

Abstract: Circulating concentrations of IGF-I and IGFBP-3 are associated with risk of pre-menopausal breast cancer. Racial differences in levels of these factors have been reported, and determinants of IGF-I and IGFBP-3 levels within racial and ethnic groups are unclear. In this study we examine genetic, anthropometric, diet, and lifestyle factors that may predict serum levels of IGF-I and IGFBP-3 among Hispanic and non-Hispanic white women. A sample of healthy controls participating in the SHINE (Southwest Hormone, Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 47 publications
10
32
0
Order By: Relevance
“…This is consistent with results from other published studies to date among men and women, and among Caucasians and Asians (33,35,37,(43)(44)(45)(46)(47)(48), suggesting that this polymorphism may be a good surrogate in the evaluation of exposure of target organs to endogenous IGFBP-3 and a good marker for the evaluation of cancer risk. Two prior studies observed a weak and statistically imprecise elevation in risk of prostate cancer associated with having the C allele (39,49).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with results from other published studies to date among men and women, and among Caucasians and Asians (33,35,37,(43)(44)(45)(46)(47)(48), suggesting that this polymorphism may be a good surrogate in the evaluation of exposure of target organs to endogenous IGFBP-3 and a good marker for the evaluation of cancer risk. Two prior studies observed a weak and statistically imprecise elevation in risk of prostate cancer associated with having the C allele (39,49).…”
Section: Discussionsupporting
confidence: 91%
“…4 It was reported that IGFBP3 could play an anti-apoptotic role in Hs578T breast cancer cells. 43 Besides, body size, vigorous physical activity, and dietary factors could influence IGF1 and IGFBP3 molar ratio in pre-menopausal breast cancer women more than postmenopausal breast cancer women, 44 and they might account for the different roles of IGF1 and IGFBP3 in breast cancer according to menopausal status.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association was found in one study [18], and no association was reported in two others [16,30]. Among studies that presented data for premenopausal women, results are also inconsistent with a positive association of the 19 allele at 5 0 and IGF-I levels suggested in one study, while no association, and an inverse association among oral contraceptive users only were also reported [10,18,31].…”
Section: Discussionmentioning
confidence: 99%